2010
DOI: 10.1007/s10518-010-9194-6
|View full text |Cite
|
Sign up to set email alerts
|

A fast method for structural health monitoring of Italian reinforced concrete strategic buildings

Abstract: The growing number of demand for a widespread of health monitoring for strategic buildings in seismic areas has emphasized the need to realize in-depth scientific studies, in order to verify the feasibility of economic and fast methods to detect anomalous vibrations, to execute post earthquake warning and monitoring, damage assessment and first damage scenarios. Generally, an effective system for structural health monitoring requires an appropriate number of sensors, suitably located in the structures, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…At the same time, as discussed in Xia et al Methodologies based on the procedures mentioned above are characterized by a limited number of sensors required to install a monitoring system on a selected structure (or infrastructure) and, at the same time, are able to provide synthetic information of the health status of the monitored structure over time (also considering information related to a possible damage occurred after an earthquake). Ponzo et al (2010) suggested a fast methodology for SHM and damage evaluation considering the accelerometric recordings provided by a single 3D accelerometric station installed on the top fl oor of the monitored structure. The procedure is based on four independent parameters (maximum top fl oor acceleration, two kinds of fundamental frequency and related equivalent viscous damping factor variations).…”
Section: Simplifi Ed Methods For Damage Detection On Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, as discussed in Xia et al Methodologies based on the procedures mentioned above are characterized by a limited number of sensors required to install a monitoring system on a selected structure (or infrastructure) and, at the same time, are able to provide synthetic information of the health status of the monitored structure over time (also considering information related to a possible damage occurred after an earthquake). Ponzo et al (2010) suggested a fast methodology for SHM and damage evaluation considering the accelerometric recordings provided by a single 3D accelerometric station installed on the top fl oor of the monitored structure. The procedure is based on four independent parameters (maximum top fl oor acceleration, two kinds of fundamental frequency and related equivalent viscous damping factor variations).…”
Section: Simplifi Ed Methods For Damage Detection On Structuresmentioning
confidence: 99%
“…1 (a) Numerical model, (b) Displacement-force behaviour for infi ll panel elements characterized by a Takeda hysteretic nonlinear behavior, while plastic hinges are characterized by an axial loaddependent one. It is possible to fi nd more details about this numerical model in Ponzo et al (2010). For multi-degree of freedom systems the dynamic equilibrium can be written as:…”
Section: Damage Location Method: Numerical and Experimental Validationmentioning
confidence: 99%
“…Impulse response functions for the S-window (IRFs, in black), and for the P-window (IRFp, in red) (i.e., IRFp) determined by deconvolving the signals Thp and Bhp, which represent an estimate of the structural response to an impulsive input. In particular, he proposed, as a first example of the decisional rule for the EEW system, that an alarm should be issued in the event that the maximum inter-story drift exceeds at one of the building's levels a threshold value of 0.5 %, which has been observed to represent a reliable threshold of damage for RC buildings (Ponzo et al 2010). 14.6a right panel).…”
Section: Real-time Early Warning and Structural Response Assessment Bmentioning
confidence: 99%
“…Link elements have a Takeda hysteretic behaviour, while plastic hinges have an axial load-dependent one. It is possible to find more details about this numerical model in Ponzo et al (2010).…”
Section: Application For Mode Shapes Evaluationmentioning
confidence: 99%